Penerapan Safe Place Technique Dalam Menurunkan Gejala Kecemasan Pada Anak Yang Mengalami Selective Mutism - Dyah Ageng Pramesty Koenarso (UIN Sultan Maulana Hasanuddin Banten, 2020)
This research focus aimed to gain an overview of the application of safe place techniques in reducing anxiety symptom for children with selective mutism. This research was conducted in TA Zam-zam Kota Malang. This research used a qualitative research with a type of case study. The data analysis technique that used was Miles and Huberman model. Data were obtained from interview, observation and analysis documents. This research found that the intervention by the teacher on N showed that the implementation of the basic principles of safe place techniques is appropriate for N because it did not directly focus on the problem of the rejection approach of speech experienced by children, this can be seen from the gesture of N who gradually began to open themselves to their surroundings. Children were not required to verbally express their feelings or emotions. Children's feelings and thoughts can be expressed through playing and drawing. Keywords: safe place technique; symptoms of anxiety; selective mutism; early childhood ReferencesAdler-Tapia, R., & Settle, C. (2016). EMDR and the Art of Psychotherapy With Children. In EMDR and the Art of Psychotherapy With Children. https://doi.org/10.1891/9780826138040American Psychiatric Association. (2000). Diagnostic and statistical manual of mental disorders : DSM-IV-TR. Wahington D.C: American Psychiatric Association.Anstendig, K. D. (1999, Juli). Is selective mutism an anxiety disorder? Rethinking its DSM-IV classification. Journal of Anxiety Disorders, Vol. 13, hal. 417–434. https://doi.org/10.1016/S0887-6185(99)00012-2Berns, R. (2013). Child, family, school, community : socialization and support. Wadsworth/Cengage Learning.Camposano, L. (2011). Silent Suffering: Children with Selective Mutism. https://doi.org/10.15241/lc.1.1.46E Shipon-Blum -. (2007). When the words just won’t come out Understanding Selective Mutism,. arnoldpalmerhospital.com.Engebretson, B. J. (2007). ANTECEDENT ANALYSIS OF VOCALIZATIONS IN CHILDREN WITH SELECTIVE MUTISM.Hess, E. B. (2009). Play-Based Intervention with Autism Spectrum Disorders (ASD).Imroatun, I. (2017). Anak Dengan Kebutuhan Fisik Khusus. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 175–185. Diambil dari http://jurnal.uinbanten.ac.id/index.php/assibyan/article/view/1347Kearney, C. A. (2010). Helping children with selective mutism and their parents : a guide for school-based professionals. Oxford: Oxford University Press.Kratochwill, T., & Serlin, R. C. (2002). Treatment of selective mutism: A best-evidence synthesis Comprehensive Health Enhancement System View project SCRIBE Guideline View project. School Psychology Quarterly, 17(2), 168–190. https://doi.org/10.1521/scpq.17.2.168.20857Krysanski, V. L. (2003). A brief review of selective mutism literature. Journal of Psychology: Interdisciplinary and Applied, 137(1), 29–40. https://doi.org/10.1080/00223980309600597Nadhirah, Y. F. (2017). Perilaku Agresi pada Anak Usia Dini. As-Sibyan : Jurnal Pendidikan Anak Usia DiniJurnal Pendidikan Anak Usia Dini, 2(2), 141–154.Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. Diambil dari https://jurnal.ucy.ac.id/index.php/agama_islam/article/view/283Vecchio, J. L. (2008). The treatment of selective mutism: A case control alternating The treatment of selective mutism: A case control alternating treatments design treatments design.